Unemployment in Europe, Structural Changes and Employment Enhancement - Balčiūnas, Norbertas (Ekonomika, 2001)
The purpose of this article is to discuss tendencies of changes in unemployment level, unemployment growth sources and labour force redistribution process. The object of this research - W. European and C&E European countries, including their differencies in income and sectoral structure. The methods of research - while doing analysis of unemployment level and labour force redistribution process and identifying main emerging principles, methods of structural analysis and balance were used. The main emphasis of the article is the influence of economy sectoral changes, labour force redistribution and expansion of foreign trade over the formation of the high unemployment level. In the end there are some conclusions and recommendations for reducing high unemployment level, first of all, in the area of structural policy.